Patient Safety Culture Among Nurses: Comparison Between Public and Private Hospital in Indonesia - Suryani, Lilis; Lindayani, Linlin (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This study aimed to describe the patient safety culture among nurses working in both public and private hospitals in Karawang, Indonesia. By examining the perceptions and practices of nurses regarding patient safety, the research sought to identify strengths and areas for improvement within the healthcare system. The findings are intended to inform strategies for enhancing patient safety practices, thereby contributing to better healthcare outcomes for patients in the region. Methods This study employed a cross-sectional methodology to investigate the patient safety culture in the intensive care units of two private and two public hospitals in Karawang, Indonesia. The researchers utilized the Hospital Survey on Patient Safety Culture (HSPSC) to gather data on nurses' perceptions and practices regarding patient safety. To analyze the data and identify any significant differences in patient safety cultural practices between the various hospital groups, both chi-square tests and independent t-tests were conducted. This approach allowed for a comprehensive assessment of the patient safety culture within the selected hospitals, facilitating comparisons between public and private healthcare settings. Results The study included a total of 118 nurses, with 52 working in a public hospital and 66 in a private hospital. The average age of nurses in the public hospital was 36.11 years (SD: 4.78), while those in the private hospital had a lower average age of 32.45 years (SD: 3.67). The results indicated a significant difference in the scores related to patient safety culture between the two groups of nurses. Specifically, nurses in the private hospital reported a higher patient safety culture compared to their counterparts in the public hospital, highlighting the disparities in perceptions and practices regarding patient safety in these different healthcare settings. Conclusion Nurses employed in private hospitals reported a higher level of patient safety culture compared to those working in public hospitals. This finding underscores the importance of creating a comfortable work environment in healthcare settings, as it is essential for minimizing the risk of patient safety incidents. By fostering a supportive and safe atmosphere, healthcare facilities can enhance the overall quality of care provided to patients and promote better outcomes in both private and public hospitals.